The Emerging Role of RNA Modifications in DNA Double-Strand Break Repair - Jimeno, Sonia; Balestra, Fernando R.; Huertas, Pablo (Frontiers in Molecular Biosciences, 2021)
The correct repair of DNA double-strand breaks is essential for maintaining the stability of the genome, thus ensuring the survival and fitness of any living organism. Indeed, the repair of these lesions is a complicated affair, in which several pathways compete for the DNA ends in a complex balance. Thus, the fine-tuning of the DNA double-strand break repair pathway choice relies on the different regulatory layers that respond to environmental cues. Among those different tiers of regulation, RNA modifications have just emerged as a promising field.